Mycobacterial HelD is a nucleic acids-clearing factor for RNA polymerase - Tomáš Kouba (Nature Portfolio, 2020)
The bacterial helicase-like transcription factor HelD associates with the RNA polymerase (RNAP) and recycles stalled transcription complexes. Here, the authors present the cryo-EM structures of three Mycobacterium smegmatis HelD bound RNAP complexes and further show that HelD can prevent the binding of the RNAP core to non-specific DNA and also actively removes RNAP from stalled elongation complexes.